Enhancing Interpersonal Communication: Lessons from 'Qaulan Sadidan' in the Quran - Kauthar Abd Kadir; Mesbahul Hoque; Norzulaili Mohd Ghazali; Robiatul Adawiyah Mohd @ Amat; Siti Mardhiyah Kamal Azhar; Shafiyah Abdul Khodir (Human Resource Management Academic Research Society, 2024)
Vol 13, Issue 12